Financial Stability, Systems and Regulation - Kregel, Jan (Routledge Critical Studies in Finance and Stability., 2018)
Ever since the 2007–8 global financial crisis and its aftermath, Hyman Minsky’s theory has never been more relevant. Throughout his career, Jan Kregel has called attention to Minsky’s contributions to understanding the evolution of financial systems, the development of financial fragility and instability, and designing the financial structure necessary to support the capital development of the economy. Building on Minsky, Kregel developed a framework to analyze how different financial structures develop financial fragility over time. Rather than characterizing financial systems as market-based or bank-based, Kregel argued that it is necessary to distinguish between the risks that are carried on the balance sheets of banks and other financial institutions. This volume, brought together by Felipe C. Rezende, highlights these major contributions from Kregel through a collection of his influential papers from various journals and conferences. Kregel’s approach provides a strong theoretical background to understand the making and unfolding of the crisis and helps us to draw policy implications to improve financial stability, and suggest an alternative financial structure for a market economy. In this book, his knowledge is consolidated and the ideas he puts forward offer a path for future developments in economics which will be of great interest to those studying and researching in the fields of economics and finance.